Direct detection of 8-oxo-dG using nanopore sequencing - Marc Pagès-Gallego; Daan M. K. van Soest; Nicolle J. M. Besselink; Roy Straver; Janneke P. Keijer; Carlo Vermeulen; Alessio Marcozzi; Markus J. van Roosmalen; Ruben van Boxtel; Boudewijn M. T. Burgering; Tobias B. Dansen; Jeroen de Ridder (Nature Communications)
Abstract Genomic DNA is under constant oxidative damage, with 8-oxo-7,8-dihydro-2’-deoxyguanosine (8-oxo-dG) being the prominent lesion linked to mutagenesis, epigenetics, and gene regulation. Existing methods to detect 8-oxo-dG rely on indirect approaches, while nanopore sequencing enables direct detection of base modifications. A model for 8-oxo-dG detection is currently missing due to the lack of training data. Here, we develop a strategy using synthetic oligos to generate long, 8-oxo-dG context-variable DNA molecules for deep learning and nanopore sequencing. Our training approach addresses the rarity of 8-oxo-dG relative to guanine, enabling specific detection. Applied to a tissue culture model of oxidative damage, our method reveals uneven genomic 8-oxo-dG distribution, dissimilar context pattern to C>A mutations, and local 5-mC depletion. This dual measurement of 5-mC and 8-oxo-dG at single-molecule resolution uncovers new insights into their interplay. Our approach also provides a general framework for detecting other rare DNA modifications using synthetic DNA and nanopore sequencing.